Fixed Output Voltage for Solar Cells Based on Buck Converter (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In order to overcome the shortcomings such asextended time and high cost of using solar cells toexperiment, this paper successfully used a DC power supplyand a variable resistor to simulate the solar cells outputcharacteristic curves. Operating principles, equivalentcircuits, and illustrative example in terms of computersimulation are presented in order to validate the approach.This paper deals the design of DC/DC converter which canmake voltage maintained at a specified value. MATLABsimulation for Open--loop and Closed--loop controlled Buckconverter for the solar cells is discussed and the results arepresented.